Association Between Body Mass Index and Meniscal Tears Requiring Surgery - Kızılgöz, Volkan; Ulusoy, Gökhan Ragıp; Aydın, Hasan; Yıldız, Kadri; Çetin, Türkhun; Evran, Mültehan (Eastern Journal of Medical Sciences, 2019)
Aim: This study evaluated the association between body mass index (BMI) and operated patients due to meniscal injuries of the knee. We also investigated the influence of BMI on meniscal tears with regard to age. Methods: We investigated 104 patients who had surgery for meniscal injuries and 111 patients who had knee magnetic resonance imaging (MRI) with no prior history of meniscal surgery. The relationship between BMI and meniscal injuries which required meniscal surgery was evaluated by independent samples T-test. A cutoff BMI value has been tried to find out by receiver operating characteristics (ROC). The odds ratio has been calculated with regard to this cutoff value. Patients were classified into three age groups ?30, 31–50 and ?51 years old. Chi-square was used to determine whether age affected the BMI relationship with meniscal injuries which required surgery. Results: BMI values were significantly higher in surgical patients compared to controls (p = 0.005). To compare surgical and non-surgical patients, ROC analysis was used and area under curve (AUC) value was calculated as 0.605. A BMI value of 27.90 had the highest specificity (92.0%) and sensitivity (40.4%), and the odds ratio calculated by Pearson chi-square was 3,08 for this BMI value. The most significant difference in BMI between surgical and non-surgical patients was observed in the 31–50 age group (p = 0.007). There was no significant difference in BMI between surgical and non-surgical patients in the